PATTERN OF PRESCRIBING PRACTICES OF TOPICAL CORTICOSTEROIDS IN THE OUTPATIENT DERMATOLOGY DEPARTMENT OF TERTIARY CARE HOSPITAL - Madarkar, MAHAJABEEN; Kambil, Srinath M; Bhat M, Ramesh; D, Sukumar (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objectives: Prescription order is an important transaction between the physician and the patient. Introduction of topical corticosteroids in the early 1950s has revolutionised dermatology which also has numerous side effects. So monitoring and analysis of the prescription practices of topical steroids can help to achieve rational prescription of these drugs. To analyze prescription patterns of topical corticosteroids in dermatology outpatient department of Father Muller Medical College, Mangalore. Methods: A cross-sectional descriptive study was conducted for a duration of 2 months from 1st January 2014 to 31st January 2014. About 200 prescriptions from drug dispensing counter was collected which was written by dermatologist. Results: Of the 751 drugs prescribed, 117 (15.4%) of all prescriptions are topical steroids. About 90 (11.8%) of the prescriptions contained very potent steroids, low potent steroids were prescribed in 16 (2.1%). Duration of applications was not mentioned in 41 (35.04%) prescriptions and site of application was mentioned 63 (53.8%) prescriptions. Conclusion: Frequent periodic prescription monitoring is an essential tool for better health care facilities. Keywords: Prescription, Topical corticosteroids, Dermatology.